2016
DOI: 10.1515/pjct-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operating parameters on production of bio-oil from fast pyrolysis of maize stalk in bubbling fluidized bed reactor

Abstract: The yield and composition of pyrolysis products depend on the characteristics of feed stock and process operating parameters. Effect of particle size, reaction temperature and carrier gas fl ow rate on the yield of bio-oil from fast pyrolysis of Pakistani maize stalk was investigated. Pyrolysis experiments were performed at temperature range of 360-540°C, feed particle size of 1-2 mm and carrier gas fl ow rate of 7.0-13.0 m 3 /h (0.6-1.1 m/s superfi cial velocity). Bio-oil yield increased with the increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…The biomass particle size was 1-2 mm. It was observed that the particle size 1 mm at 490 °C produced the bio-oil with maximum yield (42 wt%) [108] . Effect of particle size and temperature on woody biomass fast pyrolysis at high temperature (10 0 0-140 0 °C) was investigated by Septien et al They used a drop tube furnace to perform the pyrolysis experiments.…”
Section: The Effects Of Particle Size Of Biomass On Pyrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…The biomass particle size was 1-2 mm. It was observed that the particle size 1 mm at 490 °C produced the bio-oil with maximum yield (42 wt%) [108] . Effect of particle size and temperature on woody biomass fast pyrolysis at high temperature (10 0 0-140 0 °C) was investigated by Septien et al They used a drop tube furnace to perform the pyrolysis experiments.…”
Section: The Effects Of Particle Size Of Biomass On Pyrolysismentioning
confidence: 99%
“…Operation conditions were: temperature range of 360-540 °C, feed particle size of 1-2 mm and carrier gas flow rate of 7.0-13.0 m 3 /h. They concluded that the maximum yield of bio-oil was 42 wt% produced at 490 °C with the particle size of around 1.0 mm and carrier gas flow rate of 11.0 m 3 /h [108] . Wood pyrolysis in a bubbling fluid reactor was simulated by Seok et al For this aim, computational fluid dynamics (CFD) was used and the rising bubble motion and its role for pyrolysis reaction were studied.…”
Section: Bubbling Fluidised Bedsmentioning
confidence: 99%
“…Unfortunately, high-quality data for derivation of quantitative relationship between the particle size and pyrolysis yields are lacking. Ali et al reported that particle size has a linear effect on yields from pyrolysis of maize stalks in a bubbling fluidized bed reactor for particle sizes between 1 and 2 mm . However, the narrow range of particle sizes and small amount of data make it undesirable for use in developing a prediction model.…”
Section: Methodsmentioning
confidence: 99%
“…In addition Ali et al [43] performed the fast pyrolysis of maize straw in a fluidized bed reactor with feeding capacity of 2 kg/h. The maximum bio-oil yield of 42.0% was achieved at a pyrolysis temperature of 490℃ and biomass particle size of 1.0 mm.…”
Section: Comparison Of Present Work With Similar Studiesmentioning
confidence: 99%